MODELING OF LANDSLIDE SUSCEPTIBILITY IN THE CORE ZONE OF THE LORE LINDU BIOSPHERE RESERVE USING GIS - Suni, Muhammad Adam; Basoka, Muhammad Darmawan; Maarif, Fadjri; Mappatoba, Cesar Andi (Jurnal Belantara, 2025)
Landslide is a very dangerous natural disaster and often occurs in many hilly or mountainous areas, it often occurs without warning and causes loss of life and property, marked by the displacement of slope-forming material in the form of rocks, soil, or material down the slope. This study aims to model landslide-prone areas in the core zone of the Lore Lindu biosphere reserve in Central Sulawesi Province using the overlay method with a score between 6 parameters. The research parameters included land cover/use, rainfall, elevation, slope, soil type, and lithology. The weighting analysis produces three variables that determine the level of landslide vulnerability: slope, land use, and rainfall. The results showed that the level of vulnerability to landslides in the study area was divided into 4 classes, namely 17.482,15 ha (8,10%) non-prone areas, 98.372,96 ha (45,60%) low vulnerability areas, 98.032,51 ha (45,45%). moderate hazard area, and 1.832,04 ha (0,85%) high hazard area. In high vulnerability zones small or large-scale landslides often occur due to high rainfall and steep to very steep slopes, the rock forms in the form of sediment. Vegetation conditions are generally lacking. The areas included in this class are the villages of Bulili, Lawua, Sedoa, Katu, and Karunia.